Perkembangan Usaha Mikro Kecil Menengah melalui Kepuasan Nasabah: Tinjauan Lembaga Keuangan Mikro Syariah - Istifadhoh, Nurul; Saidatur Rolianah, Wiwik (Journal of Islamic Economics Studies and Practices, 2024)
This research aims to examine the role of customer satisfaction in its contribution to improving the economy in a country. So that it can be used as a basis for developing Islamic Microfinance Institutions. Customer satisfaction is a person's feeling of being satisfied and arises after an event occurs, in this case by comparing reality with the expectations they receive. The type of research used is qualitative research with a descriptive analytical approach. After observations, the result of this research is the achievement of consumer satisfaction which consists of fulfilling customer expectations, reuse in utilizing financial services and the emergence of comfort and trust which causes customers to recommend Islamic Microfinance Institutions to colleagues, family and the surrounding community. So it can be concluded that the benefits of customer satisfaction have a significant influence on improving Islamic microfinance institutions.